Pulmonary Complications after Surgery for Rectal Cancer in Elderly Patients: Evaluation of Laparoscopic versus Open Approach from a Multicenter Study on 477 Consecutive Cases. (22nd October 2017) - Milone, Marco; Elmore, Ugo; Vignali, Andrea; Mellano, Alfredo; Gennarelli, Nicola; Manigrasso, Michele; Milone, Francesco; De Palma, Giovanni Domenico; Muratore, Andrea; Rosati, Riccardo
Abstract : Aim . To evaluate the impact of open or laparoscopic rectal surgery on pulmonary complications in elderly (>75 years old) patients. Methods. Data from consecutive patients who underwent elective laparoscopic or open rectal surgery for cancer were collected prospectively from 3 institutions. Pulmonary complications were defined according to the ACS/NSQUIP definition. Results . A total of 477 patients (laparoscopic group: 242, open group: 235) were included in the analysis. Postoperative pulmonary complications were significantly more common after open surgery (8 out of 242 patients (3.3%) versus 23 out of 235 patients (9.8%); p = 0.005 ). In addition, PPC occurrence was associated with the increasing of postoperative pain (5.04 ± 1.62 versus 5.03 ± 1.58; p = 0.001 ) and the increasing of operative time (270.06 ± 51.49 versus 237.37 ± 65.97; p = 0.001 ). Conclusion . Our results are encouraging to consider laparoscopic surgery a safety and effective way to treat rectal cancer in elderly patients, highlighting that laparoscopic surgery reduces the occurrence of postoperative pulmonary complications.